Knowledge, Attitude and Practice of Health Care Professionals towards Antimicrobial Resistance and its Stewardship at Tertiary Care Teaching Hospital - Shrestha, Laxmi; Pokhrel, Sabitri; Shrivastava, Amit Kumar; Pokhrel, Buddhi Raj; Joshi, Bishal; Chhetri, Pradip (Journal of Karnali Academy of Health Sciences, 2020)
Background: Irrational antibiotic use leads to resistance, a serious problem which is increasing tremendously and requires urgent response. The goal of this study is to evaluate knowledge, attitude, and practice of health care professionals (HCPs) regarding antimicrobial resistance (AMR) and its stewardship.Methods: This questionnaire based prospective cross-sectional study was conducted in 216 HCPs of Universal College of Medical Sciences (UCMS). Chi-square analysis was used to see the association of knowledge, attitude, and practice (KAP) with other demographic variables. Pearson correlation was done to analyze the correlation between knowledge and attitude, knowledge and practice, and attitude and practice.Results: Among all participants, 33% had good knowledge, majority of them (78.2%) had positive attitude and 43.5% had good practice related to antimicrobial resistance and its stewardship. There was no significant correlation between knowledge and practice, as well as between practice and attitude. However, a weak positive correlation was found between knowledge and attitude (r=0.186; p=0.006).Conclusion: The majority of health care professionals showed a positive attitude towards antibiotic resistance and its stewardship. However, in spite of positive attitude of HCPs, the level of knowledge and practice were found to be poor.